Penerapan Green Accounting Terhadap Nilai Perusahaan Melalui Profitabilitas pada Perusahaan Sektor Energi - Rosyad Aldi Maulana; Anna Sumaryati (Faculty of Economics and Business, University of Pancasakti Tegal, 2025)
This study aims to analyze the effect of the application of green accounting on company value through profitability in the energy sector. Using a quantitative approach with test tools using WarpPLS 7.0, secondary data was collected from the annual report of 249 samples from 83 companies listed on the Indonesia Stock Exchange during 2021-2023. The results show that environmental performance has no significant effect on company value, while environmental costs and profitability have a significant influence. In addition, environmental performance and environmental costs also have a significant effect on profitability. However, profitability cannot mediate the relationship between environmental performance and environmental costs with a company's value.